The Echinococcus granulosus antigen B gene family comprises at least 10 unique genes in five subclasses which are differentially expressed. - Wenbao Zhang; Jun Li; Malcolm K Jones; Zhuangzhi Zhang; Li Zhao; David Blair; Donald Peter McManus (PLoS Neglected Tropical Diseases, 2010)
BACKGROUND: Antigen B (EgAgB) is a major protein produced by the metacestode cyst of Echinococcus granulosus, the causative agent of cystic hydatid disease. This protein has been shown to play an important role in modulating host immune responses, although its precise biological function still remains unknown. It is generally accepted that EgAgB is comprised of a gene family of five subfamilies which are highly polymorphic, but the actual number of genes present is unknown. METHODOLOGY/PRINCIPAL FINDINGS: Based on published sequences for the family, we designed specific primers for each subfamily and used PCR to amplify them from genomic DNA isolated from individual mature adult worms (MAW) taken from an experimentally infected dog in China and individual larval protoscoleces (PSC) excised from a single hydatid cyst taken from an Australian kangaroo. We then used real-time PCR to measure expression of each of the genes comprising the five EgAgB subfamilies in all life-cycle stages including the oncosphere (ONC). CONCLUSIONS/SIGNIFICANCE: Based on sequence alignment analysis, we found that the EgAgB gene family comprises at least ten unique genes. Each of the genes was identical in both larval and adult E. granulosus isolates collected from two geographical areas (different continents). DNA alignment comparisons with EgAgB sequences deposited in GenBank databases showed that each gene in the gene family is highly conserved within E. granulosus, which contradicts previous studies claiming significant variation and polymorphism in EgAgB. Quantitative PCR analysis revealed that the genes were differentially expressed in different life-cycle stages of E. granulosus with EgAgB3 expressed predominantly in all stages. These findings are fundamental for determining the expression and the biological function of antigen B.